Risk factors of poor outcome of pregnancy and delivery in adolescents: a case-control study at the Yaounde Gynaeco-Obstetric and Pediatric Hospital - Pascal, Foumane; Etienne, Belinga; Mouhaman, Hafizatou; Sama, Dohbit Julius; Esther, Ngo Um Meka; Telesphore, Mboudou Emile (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Adolescence is a period of life between 10 and 19 years, marked by a state of psychological imbalance and immaturity of organs. The occurrence of pregnancy at this age group can cause social, psychological or obstetric problems (prematurity, unsafe abortion, obstructed labor). The objective of this study was to identify the risk factors of poor outcome of pregnancy and delivery in adolescents. Methods: It was a case-control study with a retrolective data collection from January 1st, 2004 to December 31st, 2013 in the Yaounde Gynaeco-Obstetric and Pediatric Hospital. We included adolescent girls of 11 to 19 years old who delivered in the study site. We compared 128 adolescents of the case group who encountered poor outcome with 128 ones of the control groups with favorable outcome. Results: At univariate analysis, the number of antenatal care consultations less than four OR: Odds Ratio (OR= 2.44 [1.41-4.22]; P=0.000), the antenatal care consultations done out of our study site (OR= 1.65(95%CI: 1.00-2.70); p=0.003) and the uterine fundal height less than 33 cm at the time of childbirth (OR=1.80(95%CI:1.08-2.98); p=0.015) were identified as risk factors of poor outcome. After linear logistic regression analysis, the number of antenatal care less than four (OR=1.92(1.0-3.56); p=0.037) remained as independent risk factor of poor outcome. Conclusions: The number of antenatal visits less than four is an important risk factor of poor outcome of pregnancy and childbirth in adolescents at the Yaoundé gynaeco-obstetric and pediatric hospital.